Reducing sugar and aroma in a confectionery gel without compromising flavour through addition of air inclusions - Su, Katy (Food Chem, 2021)
Sugar plays an important role in both the flavour and structure of confectionery. Targets have been set to reduce sugar; however, common strategies often result in changes in flavour and consumer rejection. In this study, an approach was developed to reduce sugar in confectionery gels by aeration, without significantly affecting perceived chewiness. Gelatine based gels with a 23% and 38% reduction in density were formulated using aeration. Mean bubble size was consistent across all gels (0.05–0.06 mm). Time-intensity sensory evaluation was carried out by a trained sensory panel (n = 10). With aeration, no significant difference in overall flavour perception was observed in the 23% and 38% reduced sugar and aroma gels. Air inclusions create a greater surface area, therefore accelerating mass transfer of volatiles and release of sucrose at the food-saliva interface. Consequently, we propose that less calorie dense products can be produced without compromising flavour by using gel aeration technologies.